Ground and excited state similarity studies by means of Fukui and dual-descriptor matrices - Alcoba, Diego Ricardo (2012)
This Letter reports a quantitative study of the similarity between the Fukui matrices corresponding to the ground state and those of the first excited state of a molecular system, as well as between the dual-descriptor matrices of those states. The formulation of the Fukui and dual-descriptor matrices in the basis set representation provides a simple evaluation of similarity indices, which show that the reactivity of the excited state is reversed from that of the ground state. The dependence of these indices on the electronic correlation is studied by means of numerical determinations performed in selected systems at different theoretical levels.